2018
DOI: 10.1101/307009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct prefrontal top-down circuits differentially modulate sensorimotor behavior

Abstract: SummaryThe immense behavioral repertoire of animals necessitates mechanisms that select and suppress 15 specific actions depending on current goals. The prefrontal cortex (PFC) has been suggested to orchestrate these processes by biasing activity in its target structures, but how its vastly converging inputs and diverging outputs are coordinated to control goal-oriented actions remains unclear. Here we use a bilateral task in which mice select between symmetric but opposing actions to show that distinct output… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Recent studies have also identified the contribution of specific ACC outputs to visual behavior. Distinct subpopulations of ACC projection neurons target either the visual cortex or the superior colliculus (Huda et al ., ). Anatomical analysis using virus‐mediated disynaptic tracing revealed that these two subpopulations receive inputs from overlapping but distinct set of presynaptic areas, suggesting anatomical and functional specialization of these two output circuits (Zhang et al ., ).…”
Section: Cortical and Subcortical Roles Of Frontal Cortex In Visuomotmentioning
confidence: 97%
See 3 more Smart Citations
“…Recent studies have also identified the contribution of specific ACC outputs to visual behavior. Distinct subpopulations of ACC projection neurons target either the visual cortex or the superior colliculus (Huda et al ., ). Anatomical analysis using virus‐mediated disynaptic tracing revealed that these two subpopulations receive inputs from overlapping but distinct set of presynaptic areas, suggesting anatomical and functional specialization of these two output circuits (Zhang et al ., ).…”
Section: Cortical and Subcortical Roles Of Frontal Cortex In Visuomotmentioning
confidence: 97%
“…In agreement, we recently showed that these outputs exert context‐dependent modulation over visually guided action selection. We trained head‐fixed mice on a two‐choice visual detection task and used projection‐specific optogenetics to probe the contribution of ACC outputs to visual cortex and superior colliculus to behavior (Huda et al ., ). We found that top‐down outputs from the ACC to the visual cortex are necessary for selection of correct actions.…”
Section: Cortical and Subcortical Roles Of Frontal Cortex In Visuomotmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, while the fronto‐parietal networks typical of primates are less prominent in rodents, the rodent ACC and secondary motor areas (MOs) have been associated with comparable sensorimotor functions. Notably, a region of the rodent ACC/MOs has been described as rodent “frontal orienting field” (FOF), in putative homology to the primate FEF, given the ACC/MOs area's extensive connectivity with the SC and the visual areas (Zingg et al., 2014, but see Preuss & Wise, 2021), as well as its functional involvement in controlling eye movements (Sato et al., 2019) and other orienting actions (Ebbesen et al., 2018; Huda et al., 2020).…”
Section: Introductionmentioning
confidence: 99%